Штучний інтелект і фотожурналістика: виклики та загрози - Максимович, Мирослав; Maksymovych, Myroslav (Видавництво Львівської політехніки, 2025)
У публікації подано визначення штучного інтелекту в сучасних засобах масової інформації загалом і в фотожурналістиці зокрема. Розглянуто напрями та сфери штучного інтелекту у візуальному оформленні медійного контенту. Здійснено короткий огляд джерельної бази з проблематики дослідження. Проаналізовано погляди на залучення машинних систем у сучасних засобах масової інформації як з боку теоретиків журналістики, так і фотокореспондентів-практиків. Окреслено найважливіші аспекти професійної діяльності фотожурналіста, порушення етичних та правових норм, проблеми та виклики, з якими зіштовхуються фотожурналісти та фотокореспонденти сучасних масмедіа під час залучення штучного інтелекту до візуалізації журналістських текстів. Охарактеризовано основні чинники та властивості штучного інтелекту, які можуть бути використані в медійній сфері для створення зображень. Вказано на переваги й недоліки застосування машинних систем у сучасних засобах масової комунікації. Наголошено на законодавчих вимогах та певних заборонах щодо використання штучного інтелекту в повсякденній роботі фотожурналістів. На основі правово-нормативних документів, теоретичних узагальнень та професійних вимог виписано поради та рекомендації журналістам-практикам, які працюватимуть над оформленням текстів контентом, створеним за допомогою машинних систем. У висновках акцентовано на основних викликах та загрозах, які супроводжують продукцію штучного інтелекту в системі засобів масової комунікації.

The publication provides a definition of artificial intelligence in modern media in general and in photojournalism in particular. The directions and spheres of artificial intelligence in the visual design of media content are considered, which has become an everyday manifestation of a post-industrial society characterised by technical innovations, informatisation and digitalisation of most areas and sectors of everyday human activity. A brief overview of the source base on the research topic is made. The author analyses the views on the use of machine systems in modern mass media from both journalism theorists and practicing photojournalists. It is indicated that in modern mass media, artificial intelligence is used to search for the necessary information and facts, create messages, news and visual content, and generate various images on a given topic. It is noted that the use of artificial intelligence helps to optimise the work of journalists, automate work processes and process large amounts of information. The author outlines the most important aspects of the professional activity of a photojournalist, violations of ethical and legal norms, problems and challenges faced by photojournalists and photojournalists of modern media when using artificial intelligence to visualise journalistic texts. The article describes the main factors and properties of artificial intelligence that can be used in the media sphere to create images. The advantages and disadvantages of using machine systems in modern mass communication are indicated. The author emphasises the legal requirements and certain prohibitions on the use of artificial intelligence in the daily work of photojournalists. On the basis of legal and regulatory documents, theoretical generalisations and professional requirements, the article provides advice and recommendations for practicing journalists who will work on the design of texts with visual content created by machine systems. The conclusions focus on the main challenges and threats that accompany artificial intelligence products in the mass communication system.
Artificial intelligence and photojournalism: challenges and threats
Keywords: фотожурналістика; штучний інтелект; об’єктивність; візуалізація; віртуалізація; photojournalism; artificial intelligence; objectivity; visualisation; virtualisation; 004.8; [070; 77.03/.08]М-172